Occurrence of non-O157 Shiga toxin-producing Escherichia coli in healthy cattle and goats and distribution of virulence genes among isolates - Tayzar, A. C.; Abdul Aziz, Saleha; Abdul Mutalib, Abdul Rahim; Marimuthu, Murugaiyah; Shah, Atta Hussain (Academic Journals, 2013)
Shiga toxin-producing Escherichia coli (STEC) are receiving more attention mainly because they are zoonotic and food borne in nature. The objectives of the present study were to determine the occurrence of non-O157 Shiga toxin producing E. coli in cattle and goats and distribution of the virulence genes in the isolates. The overall isolation rates of non-O157 STEC was 15.27% (7/87) in cattle and 8.14% (22/144) in goats. Four serogroups namely O8, O26, O103 and O128 were detected. Of these serogroups, O8, O26 and O103 were common in both, cattle and goats, whereas O128 was carried by goats only. Using Duopath Verotoxin (DV) test, 52.63% of sero-positive E. coli isolates from cattle were positive for Stx1 shiga toxin whereas none of the isolates was positive for Stx2. Similarly, 42.9% (3/7) of sero-positive E. coli isolates from goats produced Stx1 and 14.3% (1/7) were positive for both, Stx1 and Stx2. The study on virulence genes showed that stx1 was commonly distributed among non-O157 STEC isolates of cattle (57.9%) and goats (57.1%).